Parenting and Social Environment in Improving Early Childhood Social Skills: A Study of Informal Education - Ulfah Mawardi; Ahmad Azhar Mawardi (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Social skills in early childhood are a crucial foundation for children's future social development and adaptation. In the context of informal education, families and communities serve as primary learning ecosystems that shape children's interaction patterns. This article aims to examine how parenting and the social environment are discussed in the literature as factors influencing children's social skill development through a narrative literature review approach. This review synthesizes reputable national and international journal articles and academic books published between 2015 and 2024. The results of the synthesis indicate that responsive parenting and a supportive social environment contribute significantly to the development of empathy, cooperation, and emotional regulation. However, these findings also demonstrate variations in outcomes influenced by differences in family context, school setting, and sociocultural conditions, confirming that there is no single approach (one size fits all). Theoretically, this article strengthens the relevance of the Integrated Developmental Ecological Model by repositioning parenting and the environment not as independent variables, but as dynamically interacting systems. The novelty of this article lies in its critical synthesis across ecological levels that emphasizes the importance of holistic synergy between strengthening domestic capacity and creating a conducive social environment for future early childhood education policies.